Cobalt-Catalyzed Aminocarbonylation of Alkyl Tosylates: Stereospecific Synthesis of Amides - Sargent, Brendon T. (Angew Chem Int Ed Engl, 2019)
Metal-catalyzed aminocarbonylation is a standard approach for installing amide functionality in chemical synthesis. Despite broad application of this transformation using aryl or vinyl electrophiles, few examples involve unactivated aliphatic substrates. Furthermore, there are no stereocontrolled aminocarbonylations of alkyl electrophiles known. Herein, we report a stereospecific aminocarbonylation of unactivated alkyl tosylates for the synthesis of enantioenriched amides. This cobalt-catalyzed transformation uses a remarkably broad range of amines in a convergent manner, and proceeds with excellent stereospecificity and chemoselectivity.